PENINGKATAN MOTIVASI BELAJAR SISWA KELAS IV PADA TEMA 2 MATERI PERUBAHAN ENERGI MELALUI MEDIA PEMBELAJARAN PAPAN PERUBAHAN ENERGI DI MI MIFTAHUL JANNAH - Faizatul Mukarromah; anggraeni dwi turnawati; korik alfat (LPPM STAI Muhammadiyah Probolinggo, 2023)
Abstract This research aims to: Increase the learning motivation of class IV students on energy change material at MI MIFTAHUL JANNAH through the energy change board learning media. The subjects of this research were class IV students at MI MIFTAHUL JANNAH. This type of research is PTK (Classroom Action Research). This research was conducted to increase student learning motivation. This energy change board learning media is used to further motivate students in studying material about energy changes in science lessons. The results of the research show that using the energy change board learning media, students are more enthusiastic and motivated in participating in learning. Apart from that, students responded very well to the use of this media.